Analisis Temporal Banjir Kabupaten Wajo 2020 – 2024: Pola Kejadian, Dampak, dan Faktor Penyebab - Shohifah Shaf; Mohammad Ikhwan Syahtaria; Christine Sri Marnani (CV. Rayyan Dwi Bharata, 2026)
Floods are the primary hydrometeorological disaster in Wajo Regency, threatening food security and human safety. This study aims to analyze the temporal patterns of flood events for the 2020–2024 period, identify regional impacts, and examine the main causal factors. The method employed is descriptive quantitative with a temporal analysis approach using secondary data from BPBD and BMKG. The results indicate fluctuations in flood events, with the highest peak occurring in 2021 (a total of 24 accumulative sub-district events). Temporally, floods consistently occur in December, January, and May. The most significant spatial impact is found in Sabbangparu District (17 events, 47,733 people affected, and 15,706 Ha of agricultural land damage), followed by Tempe and Tanasitolo Districts. Flood triggering factors are multidimensional, including extreme precipitation, embankment failure, upstream discharge accumulation in Lake Tempe, and limitations in hydraulic infrastructure. These findings recommend the need for preventive-adaptive mitigation through the improvement of flood control infrastructure integrated with time-based early warning systems to reduce disaster risks effectively.Keywords: Temporal Analysis, Flood Disaster, Wajo Regency, Mitigation, Temporal Patterns.